Effects of individual cohesion and patient interpersonal style on outcome in psychodynamically oriented inpatient group psychotherapy - Dinger, Ulrike; Schauenburg, Henning (Psychotherapy research, 2010)
The influence of patients' interpersonal traits in interaction with experienced individual cohesion (i.e., each patient's feeling of belonging to the group) was investigated in a sample of 327 inpatients with mixed diagnoses. High cohesion and an increase in cohesion emerged as predictive for symptom improvement in a multilevel regression model. This influence was moderated by the affiliation dimension: In dismissive patients, an increase of cohesion over the course of treatment was helpful; in affiliative patients, symptom improvement was correlated with a slight decrease of cohesion. The findings highlight the therapeutic importance of group therapy and point to the differential influence of individually experienced group cohesion.
Published online: 24 Jul 2009
Gesehen am 06.02.2023